Risk Factors for Bleeding and Clinical Ineffectiveness Associated With Clopidogrel Therapy: A Comprehensive Meta‐Analysis - Khoa A. Nguyen; Michael T. Eadon; Ryan Yoo; Evan Milway; Allison Kenneally; Kevin Fekete; Hyun Oh; Khanh Duong; Elizabeth C. Whipple; Titus K. Schleyer (Wiley, 2021)
Although clopidogrel is a frequently used antiplatelet medication to treat and prevent atherothrombotic disease, clinicians must balance its clinical effectiveness with the potential side effect of bleeding. However, many previous studies have evaluated beneficial and adverse factors separately. The objective of our study was to perform a comprehensive meta‐analysis of studies of clopidogrel's clinical effectiveness and/or risk of bleeding in order to identify and assess all reported risk factors, thus helping clinicians to balance patient safety with drug efficacy. We analyzed randomized controlled trials (RCTs) of maintenance use in four stages: search for relevant primary articles; abstract and full article screening; quality assessment and data extraction; and synthesis and data analysis. Screening of 7,109 articles yielded 52 RCTs that met the inclusion criteria. Twenty‐seven risk factors were identified. "Definite risk factors" were defined as those with aggregated odds ratios (ORs) > 1 and confidence intervals (CIs) > 1 if analyzed in more than one study. Definite risk factors for major bleeding were concomitant aspirin use (OR 2.83, 95% CI 2.04-3.94) and long duration of clopidogrel therapy (> 6 months) (OR 1.74, 95% CI 1.21-2.50). Dual antiplatelet therapy, extended clopidogrel therapy, and high maintenance dose (150 mg/day) of clopidogrel were definite risk factors for any bleeding. Reduced renal function, both mild and severe, was the only definite risk factor for clinical ineffectiveness. These findings can help clinicians predict the risks and effectiveness of clopidogrel use for their patients and be used in clinical decision support tools.